PERAN MATA PELAJARAN PKN DALAM MEMBANGUN KECAKAPAN SOSIAL PESERTA DIDIK - Putri, Mas Fierna Janvierna Lusie; Rosmiati, Yatti; Susi, Susi; Devi, Lathifah Sandra; Abidin, Raistin Nur (Academy of Education Journal, 2023)
The purpose of the research is to find out Cultural civilisation and scientific and technological progress are things that cannot be denied. The Indonesian nation certainly wants the advancement of development in all fields. But there are things that should not be forgotten that education as a place, place and school becomes an institution where fostering harmony between the development of science and technology with cultural, social, religious and other civilisations. One of them is the subject of Pancasila and civic education as a subject that is the main in the formation of skills, good moral, ethical, behavioural, and social skills. This research was conducted at MTS Sirajul Falah, Parung, Bogor Regency, West Java, with this research expected to build students' social skills. Civics subjects have a major role in shaping social skills for students. Social skills as skills, attitudes/behaviours of a person in communicating, interacting, socialising with the surrounding environment and life throughout time. Learners are expected to have the skills to cooperate with others, control themselves, share thoughts and experiences with others, a sense of empathy, appreciate and respect others, not bullying. However, in building social skills, there must be supporting factors for the development of students' social skills, namely teachers, students, and the environment. The inhibiting factors are family, community environment, and the impact of technological advances, the flow of incoming western culture.